Uniting the field: using the ACRL Visual Literacy Competency Standards to move beyond the definition problem of visual literacy. Issue 2 (2nd April 2020) - Thompson, Dana Statton; Beene, Stephanie
Abstract: Visual literacy has evolved alongside information literacy and media literacy, reflecting social, technological, and cultural changes. Rapidly advancing technology, multimodal access to information and disinformation, and political rhetoric increasingly impact the perception, trust, and use of visual media. These broader technological and cultural shifts also change what it means to be a visually literate individual in the twenty-first century. Although much has been written about visual literacy, there is very little that reviews scholarship that uses the 2011 ACRL Visual Literacy Competency Standards for Higher Education . Through an analysis of 196 articles published from 2011 to 2019, this study examines how the standards, which outline visual literacy competencies for learners in the twenty-first century, have been used since their adoption, by whom, and for what purposes. This study unveils an emerging shift in the paradigm of visual literacy scholarship. Abbreviations: ACRL: Association of College and Research Libraries; Visual Literacy Standards: Visual Literacy Competency Standards for Higher Education; the Standards: Information Literacy Competency Standards for Higher Education; the Framework: Framework for Information Literacy for Higher Education.